The legal status of local self-government in the field of public security - Czuryk, Małgorzata; Kostrubiec, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The vast array of responsibilities assigned to local self-government include also public security. This is all the more important as it must be ensured at every tier of administration, including in the regions. The local self-government, as the basic form of decentralised public administration, is situated closest to citizens and is therefore most responsive to their needs, with security needs being fundamental needs that must be addressed on a continuous basis.The jurisdiction of local and regional government bodies in the field of public security concerns many areas, but it is the local government which holds most of these responsibilities while the regional government is entrusted with less responsibility in this matter. This characteristic covers the institution of emergency states, crisis management, or issuing public order regulations.
Keywords: samorząd lokalny; bezpieczeństwo